Riesgo de inundación y ordenación territorial: El caso de la ley valenciana 4/2004 - Giménez Ferrer, José Manuel (Observatorio Medioambiental, 2007)
The Valencian territorial regulation framework offers many possibilities to carry out a more rational administration of the environment. Rationality understood in the appropriate use of so limited and scant resources, such as the water, the soil, the landscape and the Valencian culture. The flood and freshet risks are circumstantial problems of the Valencian geography. The 4/2004 law include these problems inside its priority objective framework for a more sustainable administration of its region. Alicante’s southern coast drainage net case is an extraordinary example of the needed intervention for this new legal framework part.